Local Wisdom of Kampung Naga in The Era of Globalization (Journal of Humanities and Social Studies, 2018)
This study aims to describe the local wisdom of Kampung Naga which is located in Tasikmalaya, West Java, is a village inhabited by a group of people who are very strong in holding the traditions of their ancestors, namely Sundanese customs. As part of the Sundanese people, Kampung Naga residents have enriched Sundanese culture that has wisdom in the local knowledge system to maintain the rituals of their lives, as a harmonization of human, natural and environmental relations. They have livelihoods besides farming, which is making crafts with bamboo raw materials. Both of these activities become the family's economic backbone to fulfill their daily needs. This society is not a primitive society or an isolated tribe, instead they are a society that has followed a modern lifestyle, but they still maintain their customs and traditions, have a mindset that is far ahead, because they are rich in philosophical teachings and values that sublime and obedient to the norms, socio-cultural values resulting from the decisions of the adat and religious deliberations in Islam. The above ceremonies are still preserved by the Kampung Naga community as indigenous communities that are full of various traditions and can be applied in their daily lives, making Kampung Naga a tourist attraction in West Java, especially for domestic tourists. and foreign countries, which ultimately affect their socio-economic fields.